ChemInform Abstract: Gallic Acid: Prospects and Molecular Mechanisms of Its Anticancer Activity. Issue 27 (18th June 2015) - Subramanian, A. P.; John, A. A.; Vellayappan, M. V.; Balaji, A.; Jaganathan, S. K.; Supriyanto, Eko; Yusof, Mustafa
Abstract Review: 95 refs.